POTRET KARAKTER POSITIF TOKOH UTAMA FILM KAASAN ORE WA DAIJOUBU - Diana, Ade; Rahayu, Nana; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Positive character portraits of the main character of the film Kaasan Ore Wa Daijoubu can help learners, especially Japanese language students, regarding the positive character potraits contained in the film Kaasan Ore Wa Daijoubu. Both in understanding the meaning and the right types of positive characters so that they can be realized in everyday life. The purpose of this study is to describe and explain what positive characters and in what situations the potential for positive characters appears in the main characters in the film. The method used is to use the observation technique and note-taking technique. The results of data analysis show that there are seven positive character potraits of the main character in the film Kaasan ore wa daijoubu based on bushido values. Bushido used to be a moral principle possessed by Japanese knights and is now a closely related character value for Japanese society.Key Words: Positive characters, film as a medium of learning, bushido.